The Iliad - Homer (Penguin classics deluxe edition., 1998)
The centuries old epic about the wrath of Achilles is rendered into modern English verse by a renowned translator and accompanied by an introduction that reassesses the identity of Homer. In Robert Fagles' beautifully rendered text, the Iliad overwhelms us afresh. The huge themes godlike, yet utterly human of savagery and calculation, of destiny defied, of triumph and grief compel our own humanity. Time after time, one pauses and re-reads before continuing. Fagles' voice is always that of a poet and scholar of our own age as he conveys the power of Homer. Robert Fagles and Bernard Knox are to be congratulated and praised on this admirable work.